2019
DOI: 10.3389/fpsyg.2019.02621
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the Cybernetic Code: Understanding and Treating the Human Metacognitive Control System to Enhance Mental Health

Abstract: The self-regulatory executive function (S-REF) model explains the role of strategic processes and metacognition in psychological disorder and was a major influence on the development of metacognitive therapy. The model identifies a universal style of perseverative negative processing termed the cognitive attentional syndrome (CAS), comprised of worry, rumination, and threat monitoring in the development of disorder. The CAS is linked to dysfunctional metacognitions that include beliefs and plans for regulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
51
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 114 publications
9
51
0
3
Order By: Relevance
“…Need for control positively and significantly correlated with ambivalence-worry and ambivalence-merger, and CSC positively and significantly correlated with ambivalence-merger. These observations are in line with a previous study that reported a relationship between metacognitive beliefs and anxious attachment style ( Myers and Wells, 2015 ) and suggests that further research should investigate the relationships between the metacognitive model ( Wells, 2019 ) and attachment theory. The results support the call for future studies that examine the development of metacognitions as specified in the metacognitive model ( Wells, 2019 ), with insecure attachments offering a candidate risk factor for dysfunction in the metacognitive control system.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Need for control positively and significantly correlated with ambivalence-worry and ambivalence-merger, and CSC positively and significantly correlated with ambivalence-merger. These observations are in line with a previous study that reported a relationship between metacognitive beliefs and anxious attachment style ( Myers and Wells, 2015 ) and suggests that further research should investigate the relationships between the metacognitive model ( Wells, 2019 ) and attachment theory. The results support the call for future studies that examine the development of metacognitions as specified in the metacognitive model ( Wells, 2019 ), with insecure attachments offering a candidate risk factor for dysfunction in the metacognitive control system.…”
Section: Discussionsupporting
confidence: 92%
“…The finding of a contribution of a range of metacognition subscales with an emphasis on negative beliefs about uncontrollability in particular fits with the metacognitive model of psychological disorder (Wells and Matthews, 1994;Wells, 2019) and potentially extends the model to understanding mechanisms of interpersonal dysfunction. In the model, beliefs concerning the uncontrollability and dangerousness of worrying are viewed as part of a common mechanism involving biased and unhelpful patterns of cognitive regulation.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Thus, the additional treatment appears to have reduced to a greater extent maladaptive metacognitive beliefs and repetitive and unhelpful coping styles, which are hypothesized mechanisms of psychological disorder. 36 …”
Section: Discussionmentioning
confidence: 99%
“…“My worrying is uncontrollable; Worrying too much will cause my cancer to return”). Negative metacognitive beliefs are considered to be of particular importance in psychological dysfunction because they lead to a sense of loss of control of thinking and a sense of current threat from cognition itself [ 23 , 28 ]. One of the features of the metacognitive model is that it is transdiagnostic, suggesting that psychological distress is maintained by a common set of processes.…”
Section: Introductionmentioning
confidence: 99%